IMPACTING ARTIFICIAL INTELLIGENT CHATBOT IN FLIPPED CLASSROOM TO ENHANCE STUDENTS’ SPEAKING COMPETENCE - Setyoningrum, Tri Yuli; Susanto, Dias Andris; Setiaji, Arso (Applied Research on English Education (AREE), 2025)
Traditional teaching methods have changed in recent years due to the integration of technology into education. The use of artificial intelligence (AI) in education has received the greatest attention. The flipped classroom concept is one area where AI has demonstrated promise. However, one challenge teacher’s face in language learning contexts is providing opportunities for          students to practice speaking skills effectively. The purpose of this study is to examine how AI Chatbots in flipped classrooms can enhance students' speaking competence. This study employed a mixed method research design. Students were split into two groups: the experimental group received instruction via an AI Chatbot before speaking class, and the control group received instruction using a conventional approach. A pre-test and a post-test were administered preceding to and following treatment, separately. Five participants were interviewed and a questionnaire was distributed to all participants in order to measure students' perceptions. The study's findings showed that teaching speaking through AI Chatbots in flipped classrooms was more effective than the conventional approach. Pupils who received instruction from an AI Chatbot in a flipped classroom were much more likely to pass KKM. The benefits of deploying AI Chatbots in flipped classrooms are also evident from students' questionnaire responses, which show that students enhanced their vocabulary, pronunciation and gained confidence. Briefly stated, AI Chatbots in flipped classroom can be utilized as a substitute for traditional classroom instruction in speaking, and they have been shown to boost students' confidence in addition to their speaking competence.